Technology, manufacturing performance and business performance amongst Australian manufacturers - Beaumont, N.B.
In 1994, the Australian Manufacturing Council completed a comprehensive survey of Australian manufacturers. The survey sought information on elements of manufacturing strategy, manufacturing practices (e.g. benchmarking and people management), manufacturing performance (quality and timeliness) and business performance (sales growth, exports and market share). An aspect of manufacturing practice was the use of advanced manufacturing technology (AMT). In this paper we report on the statistical links between the use of AMT, manufacturing performance and business performance amongst Australian manufacturers. Statistical estimates of the strength of these links depend on the assumptions made about the data. Our findings will disappoint those who hope or expect technology to be strongly associated with business success : the statistical evidence is equivocal. While noting that statistical association does not imply causation, we nevertheless suggest some plausible explanations of strong associations. More study of the ways in which human, social and organisational factors mediate the way in which technology affects organisational performance is required.
It has been suggested that improved manufacturing strategy and practices, including Advanced Manufacturing Technology (AMT) should lead to business success. The findings of this paper in support of this contention are muted at best. The authors put forward some tentative insights into the implementation of AMT and the research is ongoing.
Keywords: Manufacturers--Australia.; Manufacturing performance